2021
DOI: 10.32629/memf.v2i3.365
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Concept and Promotion Mechanism of Enterprise Economic Resilience

Abstract: The economic resilience of enterprises measures the ability of enterprises to resist the impact of negative factors and to optimize and upgrade after impact. Especially today, when the business environment of enterprises around the world is changing significantly, the significance of improving the economic resilience of enterprises is particularly prominent. Based on the theory of evolution, this paper puts forward the concept of enterprise management toughness, then further explores the promotion mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The digital economy will also promote low-carbon development from government governance and corporate transformation [ 37 ]. Zhao and Li [ 38 ] and Abidi et al [ 21 ] provide the evidence of digital transformation promotes economic resilience with micro-level research.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The digital economy will also promote low-carbon development from government governance and corporate transformation [ 37 ]. Zhao and Li [ 38 ] and Abidi et al [ 21 ] provide the evidence of digital transformation promotes economic resilience with micro-level research.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…As far as energy companies are concerned, Zhao et al [48] found that digital transformation provides large-scale information evaluation for public policies and diagnostic measures and greatly improves the efficiency of communication with people, which has a certain impact on enterprise performance. Midtun et al [49] noted that energy companies with digital transformation capabilities to integrate operations can utilize digital technology to transform their operations, enabling better customer interaction and collaboration and thereby improving business performance.…”
Section: Literature Reviewmentioning
confidence: 99%